2015
DOI: 10.3382/ps/pev282
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deposition kinetics of different selenium sources in muscle and feathers of broilers

Abstract: The objective of this study was to determine selenium (Se) deposition kinetics in muscles and feathers of broilers in order to develop a rapid method to compare bioavailability of selenium sources. Different Se sources such as 2-hydroxy-4-methylselenobutanoic acid (HMSeBA, SO), sodium selenite (SS) and seleno-yeast (SY) were compared for their kinetics on Se deposition in muscles and feathers in broiler chicks from 0 to 21 d of age. A total of 576 day-old broilers were divided into four treatments with 8 repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
11
24
0
Order By: Relevance
“…Indeed, hens fed the diet with HMSeBA at 0.2 ppm accumulated more Se in their eggs (+28.78%; P < 0.01) and muscles (+28%; P < 0.01) than those fed the diet supplemented with Se-yeast at the same level of supplementation ( Jlali et al., 2013 ). In an experiment with the growing chickens it was shown that after 21 days, organic Se sources maintained (Se-yeast) or increased (HMSeBA) ( P < 0.05) breast muscle Se concentration compared to hatch value whereas inorganic source (SS) or non-supplemented group (NC) showed a significant decrease in tissue Se concentration ( P < 0.05) ( Couloigner et al., 2015 ). Maternal Se has a long-term consequences for the developing embryo and newly hatched chicks ( Pappas et al., 2005 ).…”
Section: Antioxidant Defences Of the Developing Embryomentioning
confidence: 99%
“…Indeed, hens fed the diet with HMSeBA at 0.2 ppm accumulated more Se in their eggs (+28.78%; P < 0.01) and muscles (+28%; P < 0.01) than those fed the diet supplemented with Se-yeast at the same level of supplementation ( Jlali et al., 2013 ). In an experiment with the growing chickens it was shown that after 21 days, organic Se sources maintained (Se-yeast) or increased (HMSeBA) ( P < 0.05) breast muscle Se concentration compared to hatch value whereas inorganic source (SS) or non-supplemented group (NC) showed a significant decrease in tissue Se concentration ( P < 0.05) ( Couloigner et al., 2015 ). Maternal Se has a long-term consequences for the developing embryo and newly hatched chicks ( Pappas et al., 2005 ).…”
Section: Antioxidant Defences Of the Developing Embryomentioning
confidence: 99%
“…The same authors also found that at 21 days of age, the amount of Se in the breast muscle remained the same as that at birth in birds fed SeL, while it decreased in birds supplemented with inorganic Se and in birds that were not supplemented. The reduction of Se in the breast muscle in that work could be explained in part by Se mobilisation in the muscle through protein turnover, releasing the selenomethionine from muscle proteins (COULOIGNER et al, 2015). Conversely, the rapid breast muscle growth between 14 and 21 days of age could also explain the slight reduction of Se in the breast in birds fed SeL (COULOIGNER et al, 2015).…”
Section: Quantification Of Se In Meatmentioning
confidence: 83%
“…The reduction of Se in the breast muscle in that work could be explained in part by Se mobilisation in the muscle through protein turnover, releasing the selenomethionine from muscle proteins (COULOIGNER et al, 2015). Conversely, the rapid breast muscle growth between 14 and 21 days of age could also explain the slight reduction of Se in the breast in birds fed SeL (COULOIGNER et al, 2015). O'Grady et al (2001) found that the inclusion of dietary SeL, with or without the addition of VE, did not affect the muscle Se concentrations of beef cattle.…”
Section: Quantification Of Se In Meatmentioning
confidence: 90%
See 2 more Smart Citations